Cultural regulation of emotion: individual, relational, and structural sources - De Leersnyder, Jozefien; Boiger, Michael; Mesquita, Batja (Frontiers in Psychology, 2013)
The most prevalent and intense emotional experiences differ across cultures. These differences in emotional experience can be understood as the outcomes of emotion regulation, because emotions that fit the valued relationships within a culture tend to be most common and intense. We review evidence suggesting that emotion regulation underlying cultural differences in emotional experience often takes place at the point of emotion elicitation through the promotion of situations and appraisals that are consistent with culturally valued relationships. These regulatory processes depend on individual tendencies, but are also co-regulated within relationships—close others shape people’s environment and help them appraise events in culturally valued ways—and are afforded by structural conditions—people’s daily lives “limit” the opportunities for emotion, and afford certain appraisals. The combined evidence suggests that cultural differences in emotion regulation go well beyond the effortful regulation based on display rules.